2007
DOI: 10.1007/s00192-007-0502-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective screening for urinary tract infections in urogynaecological patients

Abstract: This study aims to test the cost-effectiveness of reagent-strip urine nitrite compared with microbiological laboratory testing for screening of urinary tract infections (UTI). The study is a retrospective review of 708 female patients who underwent cystometry during a 1-year period. Urine dipstick nitrite was used as a screening test for UTI while urine cultures were taken as an outcome. Symptoms of UTI were noted. Of 708 patients screened, 70 (9.9%) had a significant UTI. Only 32 (4.5%)of 708 patients were ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…1), recommending thresholds for women of >10 3 CFU/ml in acute uncomplicated cystitis or, in the case of complicated UTI, >10 5 CFU/ml in a voided specimen (>10 4 CFU/ml in a catheter specimen). 24 Despite this, many recent studies, in both gynaecological 25,26 and non-gynaecological 27 populations continue to use >10 5 CFU/ml as their threshold, even among symptomatic women. Indeed, the recent joint ICS/IUGA consensus document on the terminology of pelvic floor dysfunction, endorses a threshold of >10 5 CFU/ml for voided specimens in the diagnosis of UTI.…”
Section: Contemporary Practicementioning
confidence: 90%
See 1 more Smart Citation
“…1), recommending thresholds for women of >10 3 CFU/ml in acute uncomplicated cystitis or, in the case of complicated UTI, >10 5 CFU/ml in a voided specimen (>10 4 CFU/ml in a catheter specimen). 24 Despite this, many recent studies, in both gynaecological 25,26 and non-gynaecological 27 populations continue to use >10 5 CFU/ml as their threshold, even among symptomatic women. Indeed, the recent joint ICS/IUGA consensus document on the terminology of pelvic floor dysfunction, endorses a threshold of >10 5 CFU/ml for voided specimens in the diagnosis of UTI.…”
Section: Contemporary Practicementioning
confidence: 90%
“…1). 21,26 Women with frequency/urgency/nocturia without dysuria represent a different patient cohort to acutely dysuric women. The diagnostic need for pyuria in these women is poorly studied.…”
Section: Pyuriamentioning
confidence: 99%
“…Both signals are interpreted in combination, allowing for ruling-in (both positive) and -out (both negative) urinary tract infections (Whiting et al, 2006). It was shown that dipstick negative for both LE and nitrite of a clean voided urine-bag, or nappy/pad specimen can be used to rule out UTI, excluding these samples from further investigation and establishing in less than 2 min negative conclusions (Wong et al, 2008;Ducharme, 2007). A dipstick positive for either LE or nitrite provides inconclusive diagnosis and further cultures are required (negativity to the LE or the nitrite assay or both has a specificity of 92.8%).…”
Section: Resultsmentioning
confidence: 99%